Clinical and Etiological Profile of Patients with Optic Disc Edema in Tertiary Care Centre of Nepal - Shah, Ritish K (Journal of Institute of Medicine Nepal, 2019)
Introduction: Optic disc edema can be a manifestation of various neurological disorders. Identification of those causes is possible in most cases using tests like visual acuity, color vision, visual field and suitable radiological imaging. Study in Nepalese population with regard to optic disc edema is scarce. Hence this study aims to act as a guideline for evaluation of such cases and help in further studies in this regard. Methods: A descriptive, cross-sectional study was conducted in all cases of optic disc edema presenting to neuro-ophthalmology clinic of B.P. Koirala Lions Centre for Ophthalmic Studies from January 2011 to June 2012. A detailed history was obtained and proper ocular and nervous examination was done by ophthalmologist and neuro-physician. Assessment of visual acuity, color vision, contrast sensitivity and visual field along with radiological tests were done in all possible cases. Results: Out of all the cases evaluated, 38 cases where causes of optic disc edema could be established were included in the study. The commonly affected age group was 31 to 40 years (26.3%) and most of them were males. The commonest cause observed was optic neuritis (36.8%). Others were papilledema, idiopathic intracranial hypertension, toxic optic neuropathy, non-arteritic anterior ischemic optic neuropathy (NA-AION), compressive and traumatic optic neuropathy. Conclusion: Optic neuritis and papilledema should be considered as common differential diagnosis in patients with optic disc edema. NA-AION is a relatively uncommon disease among Nepalese population.